The Use Of Flocculants In Anaerobic Digestion Of Palm Oil Mill Effluent - Chew, Thean Yean (1994)
The use of flocculant in the anaerobic digestion of palm oil mill effluent (POME) was studied. The use of flocculant had enabled pelletization in mesophilic anaerobic digestion to occur within three months of start-up for the substrate which is difficult to granulate naturally. The effect of pelletization had resulted in an increase in biomass concentration and produce a good-solid-liquid separation within the digester resulting in enhanced treatment performance and the ability to tolerate higher organic loads. Various flocculants were initially tested to assess their effectiveness in forming flocs which exhibited good settling properties with no inhibitory effects on the anaerobic digestion of POME. Zetag 88N, a cationic polyacrylamide of high molecular density was found to be the most effective flocculant. Once pelletization occured, flocculant dosage was able to be discontinued without affecting the process performance.